Usage of Braille Technology devices by Learners with visual impairment - Manu, Linda (University of Cape Coast, 2024)
This study investigates the utilization of Braille Technology Devices (BTDs) among learners with visual impairment at Ghana National College, with the goal of exploring the availability, accessibility and usage of Braille technology devices and challenges they encounter. The participants were forty-five (45) in number which consisted of twenty-nine (29) learners, two (2) administrators, and fourteen (14) educators. Selection of participants was directly relevant to the research objectives, specific inclusion and exclusion criteria were applied. Purposive sampling and non-probability approach was used to select educators, administrators and LVI. The study employed a mixed method to gain a comprehensive understanding of the usage of Braille technology devices by learners with visual impairment in Ghana National College. The findings indicate that Perkins, magnifiers, recorders, slate and stylo were available in the school. It was also indicates that Braille technology devices have provided an insight into how well it supports inclusive education. The study has provided insightful information that will improve policy making, assistive technology development, and instructional practises to better help learners with visual impairments in their academic endeavours. It also serves as a valuable resource for educators, administrators, policymakers, and advocates, driving forward the agenda of inclusive and accessible education which will foster a more equitable educational landscape for learners with visual impairment.
xi,135p;,ill
Keywords: BRAILLE TECHNOLOGY; VISUAL IMPAIRMENT